MASCULINIZATION OF Betta splendens LARVAE WITH JAVA PEPPER (Piper retrofractum Vahl) EXTRACT THROUGH IMMERSION - Prayoga, Ajie; Syarif, Ahmad Fahrul; Prasetiyono, Eva; Sari, Suci Puspita (University of Lampung, 2020)
Siamese betta fighting fish (Betta splendens) is the one of exports comodity of ornamental fish in Indonesia, but the problems of culture that fish is sex ratio of female higher than male. This research aimed to evaluate the effectiveness of java long pepper (Piper retrofractum Vahl) for betta siamese fighting fish masculinizations through larval immersion. This research was designed by randomized completely design with three treatments of different java long papper doses (0,5 mg/L, 1 mg/L, and 2 mg/L), positive control (17Î±-metiltestosteron 20 mg/L), and negative control with there replications for each treatments. The treatments of java long pepper doses was given to thirty larvae (D4) through immersion during 24 hours. The research showed that java long pepper extract with dose 2 mg/L obtained the higher male ratio (59,82%) compared with dose 0,5 mg/L (45,11%), 1 mg/L (53,92%), and negative control (23,23%). Java long pepper extract with dose 2 mg/Lincreased the male ratio 36,59% compared with negative control. Java long pepper extract have no effect for survival rate of siamese betta fighting larvae during cultured.